Efficacy of autologous serum in human adipose-derived stem cells; cell markers, growth factors and differentiation - Im, W.; Chung, J-Y.; Kim, S-H.; Kim, M. (Cellular and Molecular Biology, 2011)
Human adipose-derived stem cells (hASCs) are a feasible source of stem cells for use in clinical applications. hASCs are typically cultured in medium containing fetal bovine serum (FBS); however, use of FBS is not recommended due to issues of clinical safety with regard to infections or immune response. Replacement of FBS with autologous human serum (autoHS) can eliminate these problems; however, their maintainability as potent ASCs in autoHS needs to be confirmed. Thus, we conducted an investigation of characterizations and functions of hASCs grown in medium containing autoHS compared to FBS. Cell counting and the WST-8 assay were used in assessment of the proliferation rate. In hASC cultured with culture medium plus autoHS or FBS, cell phenotypes were characterized by flow cytometry (CD13, CD29, CD31, CD34, and CD44) and expression of BDNF, HGF, IGF, LIF, NGF, and VEGF was determined by RT-PCR. Adipogenic differentiation was confirmed by oil red O stain. hASC showed greater expansion in AutoHS than in FBS. Cell surface markers of hASCs grown in autoHS (autoHS-hASCs) were similar to markers of those grown in FBS (FBS-hASCs). AutoHS-hASCs also expressed multiple growth factors as well as FBS-hASCs. In addition, autoHS was effective in growth of hASCs as well as FBS and autoHS-hASCs retained their ability for adipogenic differentiation. In summary, autoHS-hASCs have multiple growth factor expressions with the same cell surface markers as FBS-hASCs in vitro. Our results suggest that autoHS can provide sufficient ex vivo expansion of hASCs.